Evaluating the nutritional, therapeutic, and economic potential of Tetragonia decumbens Mill.: A promising wild leafy vegetable for bio-saline agriculture in South Africa - Sogoni Avela; Jimoh Muhali Olaide; Ngxabi Sihle; Kambizi Learnmore; Laubscher Charles Petrus (Open Agriculture)
Avela Sogoni.